New class of code with any desired cross correlation for OCDMA systems - Mohd Rashidi, Che Beson; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Farid, Ghani, Prof. Dr.; Anuar, Mat Safar, Ir. Dr.; Hilal Adnan, Fadhil, Dr.; Amir Razif Arief, Jamil Abdullah, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/